2022
DOI: 10.1371/journal.pone.0265625
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differentiation in East African ethnicities and its relationship with endurance running success

Abstract: Since the 1960s, East African athletes, mainly from Kenya and Ethiopia, have dominated long-distance running events in both the male and female categories. Further demographic studies have shown that two ethnic groups are overrepresented among elite endurance runners in each of these countries: the Kalenjin, from Kenya, and the Oromo, from Ethiopia, raising the possibility that this dominance results from genetic or/and cultural factors. However, looking at the life history of these athletes or at loci previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 97 publications
0
5
0
Order By: Relevance
“…Like the present study, a study in diverse populations conducted in the literature reported that none of the SNPs reached genome-wide significance with the endurance athlete status [ 14 ]. Nonetheless, others reported the associations of the specific SNPs with different exercise-related parameters [ 15 , 16 , 17 , 45 , 46 , 47 , 48 ]. However, the number of participants in those studies was increased by the involvement of the athletes from close countries.…”
Section: Discussionmentioning
confidence: 99%
“…Like the present study, a study in diverse populations conducted in the literature reported that none of the SNPs reached genome-wide significance with the endurance athlete status [ 14 ]. Nonetheless, others reported the associations of the specific SNPs with different exercise-related parameters [ 15 , 16 , 17 , 45 , 46 , 47 , 48 ]. However, the number of participants in those studies was increased by the involvement of the athletes from close countries.…”
Section: Discussionmentioning
confidence: 99%
“…In this review, several regions were underrepresented, with Brazil being the only country included from South America, Australia the only country from Oceania and no countries included from Africa. The lack of representation in African countries appears disproportionate when considering the number of athletes from this region; for example, endurance running is dominated by Ethiopian and Kenyan athletes ( 68 ) . The lack of funding in this region may explain the absence of studies in this region.…”
Section: Discussionmentioning
confidence: 99%
“…Narratives about genetic characteristics, morphology, and physiological parameters (i.e., maximum oxygen consumption, metabolic efficiency, and hematological parameters) were debated for many years (Wilber and Pitsiladis, 2012 ; Tucker et al, 2013 ). However, a recent comparative study investigating the relationships between ethnicities (Kalenji's—Kenya and Oromo—Ethiopia) and endurance running success concluded that causality inferences regarding the relationship between genetics and sports must be avoided, once it is both scientifically incorrect and prone to reinforcing population (racial) stereotyping (Hamilton, 2000 ; Zani et al, 2022 ). With this conclusion, the authors do not exclude the role of genetics but reinforce the importance to move forward.…”
Section: Moving Beyond the Athletes- Centered Approachmentioning
confidence: 99%
“…In the context of endurance running, aside from genetic, morphological, physiological, and training characteristics that contribute to the African runner's phenomenon (i.e., Kenya, Ethiopia) (Larsen, 2003 ; Zani et al, 2022 ), the country's historical background, the population's lifestyle characteristics, the economic development, and perspectives of social ascension and/or better living conditions through the sport need to be considered as factors related to the running training engagement and performance (Bale and Sang, 1996 ). For example, colonization, religious missions, and school policies were important agents in the dissemination of running in the Kenyan context.…”
Section: Moving Beyond the Athletes- Centered Approachmentioning
confidence: 99%
See 1 more Smart Citation